2018
DOI: 10.1016/j.vaccine.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose varicella vaccine effectiveness in Brazil: A case-control study

Abstract: Effectiveness of single dose varicella vaccine in Brazil is comparable to that in other countries where breakthrough varicella cases have also been found to occur. The goal of the varicella vaccination program, along with disease burden and affordability should be taken into consideration when considering the adoption of a second dose of varicella vaccine into national immunization programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
0
15
0
5
Order By: Relevance
“…Varicella incidence data in São Paulo, Brazil, from 2002 to 2017 show a trend to increasing numbers of cases up to introduction of vaccination in 2013 (25,052), with a fall in cases in subsequent years (2822 in 2017) [58]. A case-control study of children aged 15–35 months, following the national introduction of varicella vaccination in Brazil in 2013 for children at age 15 months, showed the effectiveness of single-dose vaccine to be 86% for disease of any severity and 93% for moderate/severe cases [45]. There was a breakthrough rate of 22%, potentially attributable to vaccine failure, as the cases had been vaccinated only 9 months before, on average; patients with breakthrough varicella had less severe disease than non-breakthrough cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Varicella incidence data in São Paulo, Brazil, from 2002 to 2017 show a trend to increasing numbers of cases up to introduction of vaccination in 2013 (25,052), with a fall in cases in subsequent years (2822 in 2017) [58]. A case-control study of children aged 15–35 months, following the national introduction of varicella vaccination in Brazil in 2013 for children at age 15 months, showed the effectiveness of single-dose vaccine to be 86% for disease of any severity and 93% for moderate/severe cases [45]. There was a breakthrough rate of 22%, potentially attributable to vaccine failure, as the cases had been vaccinated only 9 months before, on average; patients with breakthrough varicella had less severe disease than non-breakthrough cases.…”
Section: Resultsmentioning
confidence: 99%
“…Five published studies reported data on the complications associated with varicella in LAC (see Additional file 3). Three studies provided data for Brazil [31, 32, 45] and one study each for Argentina [26] and Uruguay [15].…”
Section: Resultsmentioning
confidence: 99%
“…In vaccinated patients, the literature reports that, if the vaccine fails, they tend to develop milder conditions. 29,30 A recent meta-analysis on the effectiveness of the varicella vaccine showed 81% protection against all forms of the disease and 98% against moderate and severe forms. 29 The main limitation of this study was the lack of information about the patients' vaccination status.…”
Section: Discussionmentioning
confidence: 99%
“…The hospital databases did not include information on varicella vaccination, and therefore we could not identify possible varicella breakthrough cases. However, breakthrough varicella cases usually have a milder course of disease than in unvaccinated children [35,48] and therefore rarely result in hospitalization. A recent literature review outlined that only about 0-4% of VRHs were breakthrough varicella cases, based on results from 12 studies in 9 countries [49].…”
Section: Discussionmentioning
confidence: 99%